The association between a body shape index and depressive symptoms: a cross-sectional study using NHANES data (2011–2018) - Zhang, Zheng; Ruan, Xiang-Yan; Ma, Wei (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to explore the relationship between A Body Shape Index (ABSI) and depressive symptoms, and to evaluate the moderating effects of sociodemographic, lifestyle, and health factors.MethodsWe analyzed data from 19,659 participants in the 2011–2018 National Health and Nutrition Examination Survey (NHANES). Depressive symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9). ABSI was calculated from waist circumference, height, and BMI. Multiple linear regression models were employed to investigate the association between ABSI and depressive symptoms, with subgroup analyses to examine potential associations within specific populations.ResultsHigher ABSI was significantly associated with increased depressive symptoms, after adjusting for covariates including age, sex, race, marital status, poverty-income ratio, smoking, alcohol consumption, physical activity, diabetes, and hypertension. Individuals in the highest ABSI quartile (Q4) had significantly more depressive symptoms compared to those in the lowest quartile (Q1) (β = 0.22, 95% CI = 0.02–0.41, p = 0.0323). Subgroup analyses revealed that marital status and hypertension significantly moderated the association between ABSI and depressive symptoms.ConclusionThis study provides the first comprehensive analysis of the link between ABSI and depressive symptoms, suggesting that higher ABSI is associated with greater depressive symptoms. These findings highlight the potential importance of waist circumference and abdominal fat distribution in assessing depression risk. Future research should explore the causal mechanisms underlying this association and investigate the biological pathways involved, to inform more effective strategies for depression prevention and intervention.